Design a Compact Coplanar Wideband Antenna Used in Radio Frequency Identification Systems - Ali, Sufyan Hazaa; Reja, Ahmed Hameed; Hachim, Yousif Azzawi (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this paper, a new compact coplanar antenna used for Radio frequency identification (FID) applications is presented. This antenna is operated at the resonant frequency of 2.45 GHz. The proposed antenna is designed on an epoxy substrate material type (FR-4) with small size of (40 × 28) mm2 in which the dielectric thickness (h) of 1.6 mm, relative permittivity (er) of 4.3 and tangent loss of 0.025. In this design the return loss is less than −10 dB in the frequency interval (2.12 − 2.84) GHz and the minimum value of return loss is -32 dB at resonant frequency. The maximum gain of the proposed antenna is 1.22 dB and the maximum directivity obtained is 2.27 dB. The patch and the ground plane of the proposed antenna are in the same surface. The proposed antenna has a wide bandwidth and omnidirectional radiation pattern with small size. The overall size of the compact antenna is (40 × 28 × 1.635) mm3. The Computer Simulation Technology (CST) microwave studio software is used for simulation and gets layout design.